Emerging and re-emerging viruses in Malaysia, 1997-2007. - Tee, K.K.; Takebe, Y.; Kamarulzaman, A. (2009)
Over the past decade, a number of unique zoonotic and non-zoonotic viruses have emerged in Malaysia. Several of these viruses have resulted in significant morbidity and mortality to those affected and they have imposed a tremendous public health and economic burden on the state. Amongst the most devastating was the outbreak of Nipah virus encephalitis in 1998, which resulted in 109 deaths. The culling of more than a million pigs, identified as the amplifying host, ultimately brought the outbreak under control. A year prior to this, and subsequently again in 2000 and 2003, large outbreaks of hand-foot-and-mouth disease due to enterovirus 71, with rare cases of fatal neurological complications, were reported in young children. Three other new viruses - Tioman virus (1999), Pulau virus (1999), and Melaka virus (2006) - whose origins have all been linked to bats, have been added to the growing list of novel viruses being discovered in Malaysia. The highly pathogenic H5N1 avian influenza has also been detected in Malaysia with outbreaks in poultry in 2004, 2006, and 2007. Fortunately, no human infections were reported. Finally, the HIV/AIDS epidemic has seen the emergence of an HIV-1 recombinant form (CRF33_01B) in HIV-infected individuals from various risk groups, with evidence of ongoing and rapid expansion.